(untitled) (Research, Society and Development, 2021)
The storage stage is seen as one of the most important and indispensable stages within the post-harvest stages of grains and seeds. Inadequate storage and the appearance of pathogenic agents directly affect the health and durability of the grains, causing significant losses in productivity. Therefore, the work aimed to analyze the main forms of storage and packaging used by family farmers and the main difficulties faced by them in the northeast region of Pará. The main grains produced by family farmers are beans, corn, rice and coffee, a culture that has great cultural and economic expression, considering that all of these compose as a basis for human and animal feed. Storage in rural properties is of great importance, since it brings many benefits to the producer, such as marketing with higher profits, since it can be stored and sold in periods of lower supply, reducing post-harvest losses due to pest attacks, diseases and changes in temperature and humidity. Despite the practice of storage being extremely important, most rural producers still use rudimentary techniques and improvised structures, which are usually unsuitable for the correct conditioning of the grains.